Анализ несущих конструкций 19-дюймовой и метрической систем для электронных средств - Yefimenko, A. A.; Karlangach, A. P. (PE "Politekhperiodika", Book and Journal Publishers, 2015)
The paper deals with the research and analysis of various quality indicators of the standard mechanical structures of two constructional systems in order to define and compare their characteristics, and to predict prospects for their use.To compare these two systems, we have selected parameters which make it possible to make a quantitative assessment and can be calculated on the basis of the data from standards for such mechanical structures.Research has shown that, according to considered indicators, neither the 19-inch system nor the metric system has the absolute advantage. And only in the density ratio of contacts of output electrical connectors, the metric system has real advantages. Although, it should be noted, that certain measures are taken by the developers to improve the 19-inch constructional system. This may, to some extent, explain the fact that the 19-inch system is more widely used than the metric one, and continues to evolve and develop.For other indicators, which are more difficult to be assessed quantitatively, the metric system is more preferable, because it is more convenient in unit design consisting in establishment of interrelation between the coordinating sizes and basic, multiple and mounting steps. At the same time, the 19-inch system has no rival in technical readiness of the industry and in adaptation to the previous designs. The latter is the defining factor for choosing a constructional system by developers of electronic equipment. This, in turn, does not stimulate producers of mechanical structures to extend their production range in accordance with the standards of the metric system.On the basis of the analysis, we can predict that in the immediate future the 19-inch dimensional system will retain priority for the mechanical structures of electronic equipment. This project deals with the problem of determination of optimum sizes of printed circuit boards for standard mechanical structures for various electronic devices.